How cognitive behavioural therapy helps on addictive behaviour? - Mohamad Yusop, Yusni (Human Resource Management Academic Research Society, 2021)
One of the well-known theories applied in the group counselling session is Cognitive Behavioural Therapy (CBT). This article explores the systematic literature reviews on the benefit of using CBT in group counselling among clients who were having issues with drugs. This systematic literature review is managed through the following Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) guidelines. The Emerald, ProQuest Electronic and Cambridge University Press are used. This research utilized the Google Scholar website too. The term “drug”, “abuse”, “effect”, “group counselling” and other relevant derivations used in web searching. Only 10 most relevant journal articles were extracted and reviewed. Findings showed that there were positive effects of CBT in group counselling on drug abused group members. The findings suggested that Cognitive Behavioural Therapy is effective in changing the perceptions and behaviours of drug addicts, controlling anger and increasing self-esteem. CBT may raise the sense of self-awareness as well as increased confidence not to relapse after they have been released from the rehab centre. Application of CBT in group counselling helped counsellor to propose the action plan properly, which involves several steps such as identifying the level of client motivation, risky situations, client relapse processes, client situations in making irrelevant decisions, cognitive factors related to relapse, and lifestyle changes. In conclusion, it is proved that group counselling benefits in accordance with CBT application during the session to help clients have a better view of life after they recover from drug addiction.